2018
DOI: 10.1002/chem.201804066
|View full text |Cite|
|
Sign up to set email alerts
|

Insight into the Mechanochemical Synthesis and Structural Evolution of Hybrid Organic–Inorganic Guanidinium Lead(II) Iodides

Abstract: The in situ investigations of the mechanochemical synthesis of four hybrid organic-inorganic lead(II) iodides with the formula (C(NH ) ) PbI (n=1, 2, 3, and 4) are presented. Synchrotron X-ray diffraction data show that the four guanidinium lead(II) iodides easily convert into each other. Although the end product is dictated by the initial stoichiometry, complex pathways were found with different behaviors of the compounds in terms of nucleation, growth, and intermediate formation. This appears to be linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Although this compound can be seen as a 0D structure due to the fact that adjacent SnI 6 octahedra do not share any corners, their vicinity and consequent orbital overlap results in interesting optoelectronic properties for PV . Mechanochemical synthesis via ball‐milling or other techniques (e.g., hand grinding) provides an ideal platform to form a wide variety of perovskites in stoichiometric and solvent‐free conditions …”
Section: Introductionmentioning
confidence: 99%
“…Although this compound can be seen as a 0D structure due to the fact that adjacent SnI 6 octahedra do not share any corners, their vicinity and consequent orbital overlap results in interesting optoelectronic properties for PV . Mechanochemical synthesis via ball‐milling or other techniques (e.g., hand grinding) provides an ideal platform to form a wide variety of perovskites in stoichiometric and solvent‐free conditions …”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing number of TRIS synchrotron studies being reported, the collection of quality diffraction data has proved a difficult task with conventional setups and data collection strategies. 12,32,33 An innovative and highly successful solution was presented by Ban et al 34,35 who improved the signal to background ratio using a new design of milling jar. In their design, the X-ray beam was focused through a specially designed sampling chamber on the outer circumference of the milling jar, with small width and narrow walls.…”
mentioning
confidence: 99%
“…In the past, the mechanochemical synthesis of different halide perovskites has been demonstrated, including almost all combinations of the organic A-site cations MA + or FA + and X-site halides Cl -, Bror I in the case of ternary lead halide perovskites, as well as multinary mixtures thereof. [22][23][24][25] The successful introduction of additional cations, such as guanidinium (Gua + ), [26,27] rubidium (Rb + ), [28] and especially cesium (Cs + ), [20,29,30] via mechanochemistry extends the range of available stoichiometries, including the mechanochemical synthesis of the completely inorganic halide perovskites CsPbX 3 . [31][32][33] By the addition of appropriate organic molecules, it is possible to synthesize perovskite nanocrystals.…”
Section: Mechanochemical Synthesismentioning
confidence: 99%